Utilizing E-Marketing to Increase Sales in Pasireurih Village MSMEs in the Covid-19 Pandemic - Siti Aisyah, Dini; Marlina, Asti (Universitas Ibn Khaldun, 2022)
The COVID-19 outbreak has now become a global pandemic after it was announced by the World Health Organization (WHO). The negative impact of this pandemic shows that this pandemic has caused many MSMEs difficulties. Almost all sectors are affected, not only health, the economic sector is also seriously affected by this pandemic. In particular, it has an impact on Sandal SMEs in Pasireurih Village, which experienced a decline in sales. The purpose of this study is to provide solutions to SMEs in marketing their products online by using e-marketing to increase sales of sandals production in Kampung Pasireurih during the COVID-19 pandemic. through the Instagram app. This study uses descriptive qualitative methods of observation, interviews, and documentation studies (journals related to research). The results of this study researchers provide solutions to help SMEs by creating business accounts through the Instagram application. With the solution that the researchers put forward, it is hoped that SME players will be able to make the best use of e-marketing to increase sales, expand market reach, and be motivated to continue using the online marketing system as a means of communication and promotion by utilizing social media so that they are able to survive the COVID-19 pandemic situation.